A DETAILED MORPHOMETRIC STUDY OF THORACIC VERTEBRAE ANATOMY: UNDERSTANDING THE VARIATIONS IN VERTEBRAL STRUCTURE AND THEIR IMPORTANCE FOR SPINAL SURGERY AND TREATMENT OF SPINAL DISORDERS - KHAN , QUA; ASGHAR , SS; MALIK, F; NOREEN , N; AKHTAR , N; SABA , N (Biological and Clinical Sciences Research Journal, 2024)
Thoracic vertebrae anatomy is critical for understanding spinal mechanics and for surgical interventions in treating spinal disorders. Morphometric variations in vertebral structure can influence the outcomes of spinal surgeries and the management of various spinal conditions. Objective: This study aims to provide a detailed morphometric analysis of thoracic vertebrae, focusing on the variations in vertebral structure. The goal is to enhance the understanding of these variations and their implications for spinal surgery and treatment. Methods: This analytical study was conducted at the Private Hospital of Karachi from Feb 2024 to August 2024. Data were collected from 85 patients. Utilizing morphometric methodology, different parameters of morphometric dimensions were conducted and screened to reveal patterns and variations among the sample. Results: Data were collected from 85 patients, which indicates a progressive increase in vertebral body dimensions from T1 to T12, with height, width, and depth all showing a notable rise as one moves down the thoracic spine. Specifically, vertebral body height increases from 15.5 mm at T1 to 23.2 mm at T12, while width and depth expand from 24.3 mm to 34.7 mm and 20.1 mm to 30.8 mm, respectively. This gradual increase suggests an adaptation to greater load-bearing demands in the lower thoracic region, likely providing enhanced structural support as the spine transitions toward the lumbar area. Conclusions: The observed morphometric variations in thoracic vertebrae have significant implications for spinal surgery, particularly in areas like implant design and surgical approach. A comprehensive understanding of these structural differences can aid in improving surgical outcomes and in developing personalized treatment strategies for spinal disorders.